Characterization of the Vertical Structure of Coastal Atmospheric Boundary Layer over Thumba (8.5∘N, 76.9∘E) during Different Seasons. (1st June 2011) - Nair, Sandhya K.; Anurose, T. J.; Subrahamanyam, D. Bala; Kumar, N. V. P. Kiran; Santosh, M.; Sijikumar, S.; Mohan, Mannil; Namboodiri, K. V. S.
Abstract : Vertical profiles of meteorological parameters obtained from balloon-borne GPS Radiosonde for a period of more than two years are analyzed for characterization of the coastal atmospheric boundary layer (CABL) over Thumba (8.5 ∘ N, 76.9 ∘ E, India). The study reports seasonal variability in the thickness of three different sublayers of the CABL, namely, mixed layer, turbulent flow, and sea breeze flow. Among the three, the vertical thickness of sea breeze flow showed considerable dominance on the other two throughout the year. Mixed layer heights derived through gradients in virtual potential temperature (θ v ) showed large seasonal variability with a peak in the Summer and Post-Monsoon. On the other hand, the vertical thickness of turbulent flow remained steady all through the year. Results from the present study indicate that the magnitudes of mixed layer heights are often larger than the turbulent flow thickness.